Systems Thinking dan System Dynamics Sebagai Suatu Pendekatan dalam Pengukuran Kinerja Pelayanan - Dr. Endang Wirjatmi Trilestari (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
Several dimensions of public service performance appraisal carried out in Indonesia, such as the Performance Accountability Report of Government Institution (LAKIP), Index of Human Resource Development, are still oriented to the internal and partial paradigm of parties and using a good governance paradigm is unavailable. Therefore, this paper is aimed at an approach of public service performance appraisal that can fulfill the requirements of good governance paradigm by using the systems thinking and system dynamics. This approach is generally used to solve argumentative problems. Compared with other mentioned approaches, systems thinking and system dynamics are more comprehensive in dealing the problems in the following ways: (1) the model resulted can cover all fundamental variables in terms of government and people perspectives used to solve a problem of detail complexity, (2) the approach can explain the involvement the essential variables to solve a problem of dynamic complexity, (3) Variables used are transformed into a model at the same time through soft variables, hard variables and performance variables. Therefore, the process can result in a comprehensive model of performance appraisal of which its success can be detected